1975
DOI: 10.1063/1.88014
|View full text |Cite
|
Sign up to set email alerts
|

Optical waveguides in LiNbO3 by ion exchange technique

Abstract: Optical waveguides produced in LiNbO3 by immersing the x-cut plates into molten AgNO3 are reported. An increase in the extraordinary refractive index of LiNbO3 at the surface of the plate due to silver exchange is estimated to be 0.12. In such a waveguide, optical losses of 6 dB/cm were measured for the highest-order mode; losses were higher for the lower-order modes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0
1

Year Published

1975
1975
2022
2022

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(7 citation statements)
references
References 8 publications
0
6
0
1
Order By: Relevance
“…116,[121][122][123][124][125][126] Other than PE, a few other ions have also been used in such an exchange process with lithium to realize a refractive index change in LN. [127][128][129][130] ion-in diffusion, the PE method still has certain advantageous application scenarios, especially to assist dry/wet etching technologies to realize some innovative photonic devices. 131…”
Section: Proton Exchangementioning
confidence: 99%
“…116,[121][122][123][124][125][126] Other than PE, a few other ions have also been used in such an exchange process with lithium to realize a refractive index change in LN. [127][128][129][130] ion-in diffusion, the PE method still has certain advantageous application scenarios, especially to assist dry/wet etching technologies to realize some innovative photonic devices. 131…”
Section: Proton Exchangementioning
confidence: 99%
“…According to [ 13 ] the low-energy electrons (< 50 eV) lose their energy predominantly by plasmon production. Following its creation, the plasmon decays rapidly into electron-hole pairs.…”
Section: Secondary Electron Energy Distribution Functionmentioning
confidence: 99%
“…Ion exchange, widely used to produce optical waveguides in glasses, was first used experimentally by Shah [39] to fabricate lithium niobate waveguides. He found that after immersing x-cut LiNbO 3 crystals in silver nitrate at 360°C for several hours ($s3 h) a silver/lithium ion exchange occurs.…”
Section: Ion Exchangementioning
confidence: 99%